Optimalisasi Penjualan Melalui Analisis Data Transaksional Pada Database Chinook - Megalia Safitri; Sunoto, Akwan; Xaverius Sika (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
In today's digital era, data has become a strategic asset crucial for companies in decision-making processes. The Chinook database is a relational database designed to manage data for digital music sales companies. This project aims to explore and analyze data from the Chinook database, which contains information on sales, customers, artists, albums, and music genres that contribute the most to revenue. The analysis process begins with building an ETL (Extract, Transform, Load) pipeline to prepare the data into a more structured data warehouse. The data is then visualized through an interactive dashboard using Tableau. The interactive visualization on the dashboard enables business teams to make data-driven decisions to improve revenue and operational efficiency. This project provides technical benefits such as skill development in database management, ETL processes, and data visualization, as well as business benefits, including more effective marketing strategies and catalog optimization. Thus, this project not only contributes to technical development but also identifies best selling products, improves customer retention, and supports strategic decision making in the digital music industry